Social situations in Al Dhaid: for the period of (1971-2015) - AlHafri, Bshayer Ali Hamad; Al-Leheabi, Saleh Muhammad Zeki Mahmood (Al-Adab Journal, 2021)
The city of Al Dhaid, in the Emirate of Sharjah, has witnessed development in various aspects of life. It has become a city full of architecture and services. In this research, we will shed light on how the social conditions in the city of Al Dhaid have developed from 1971 to 2015 AD, so that it constituted a remarkable change in different aspects of life, as we studied the following topics: In the first topic, "The social conditions of the individuals, the family and the tribe in the city of Al Dhaid, we explained the Badiah (the desert area) of Al Dhaid, its location, population and environment. As for the second topic, we will discuss the customs, traditions and conventions of the city of Al Dhaid. And finally, in the third topic we discussed the role of social services department in serving the city, and indicating the health and educational services.